2020
DOI: 10.2105/ajph.2019.305375
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress in Solitary Confinement: Symptoms, Severity, and Prevalence in the United States, 2017–2018

Abstract: Objectives. To specify symptoms and measure prevalence of psychological distress among incarcerated people in long-term solitary confinement. Methods. We gathered data via semistructured, in-depth interviews; Brief Psychiatric Rating Scale (BPRS) assessments; and systematic reviews of medical and disciplinary files for 106 randomly selected people in solitary confinement in the Washington State Department of Corrections in 2017. We performed 1-year follow-up interviews and BPRS assessments with 80 of these in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 21 publications
3
98
0
4
Order By: Relevance
“…Reductions in institutional movement and lockdowns are likely to have resulted in decreased access to exercise, movement, and mobility, an especially important consideration for older incarcerated adults (Prost et al, 2020). Moreover, research indicates the physical and psychological harms of solitary confinement are severe and include sensory hypersensitivity and loss of identify (Reiter et al, 2020), post-traumatic stress disorder (Hagan et al, 2018), and chronic somatic diseases (Gamman, 1995;Haney, 2003). We encourage future scholars to explore how efforts to quarantine large numbers of incarcerated individuals during the pandemic may have increased exposure to solitary confinement-like living conditions for incarcerated persons, both in practice and in its effects.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in institutional movement and lockdowns are likely to have resulted in decreased access to exercise, movement, and mobility, an especially important consideration for older incarcerated adults (Prost et al, 2020). Moreover, research indicates the physical and psychological harms of solitary confinement are severe and include sensory hypersensitivity and loss of identify (Reiter et al, 2020), post-traumatic stress disorder (Hagan et al, 2018), and chronic somatic diseases (Gamman, 1995;Haney, 2003). We encourage future scholars to explore how efforts to quarantine large numbers of incarcerated individuals during the pandemic may have increased exposure to solitary confinement-like living conditions for incarcerated persons, both in practice and in its effects.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of six of these studies was ranked as moderate and two as low quality. Regarding depression and dysthymia, three studies with moderate quality evidence found higher scores in inmates having been exposed to SC (52)(53)(54). However, low quality evidence from two other studies (30,55) and one study with moderate quality evidence (51) did not observe differing depression scores between groups.…”
Section: Systematic Reviewmentioning
confidence: 95%
“…WADOC is a mid-sized state prison system, with the 12 th lowest rate of incarceration of the 50 United States [20]. The state and its prison system have a reputation for being progressive,…”
Section: Settingmentioning
confidence: 99%
“…Some researchers, however, have argued that the psychological harms of solitary confinement are limited or unverified [18,19]. The analyses on which such opinions rely have, in turn, been criticized for neglecting existing literature and for other serious methodological concerns, including an inability to isolate exposure to solitary confinement, lack of specificity about variability and comparability in actual conditions of confinement, and the inapplicability of psychological assessment scales in the prison context [1,20].…”
Section: Introductionmentioning
confidence: 99%